Extremal topological indices and their applications in drug design - Bilal Ahmad Rather (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. Topological indices are the real numbers related to structure of graphs. We consider the Sombor topological index for p-type graphs and carry its deep analysis, characterize graphs with extremum values and order them on the basis of the Sombor index/energy. Also, we give QSPR analysis of some allergy drugs with the various topological indices, study their correlation coefficient, coefficient of determination, linear, polynomial and logarithmic analysis. A significant observation is that a better relation exists between physical properties of drugs with these indices which in turn improves their efficiency and advances their design structure.
Keywords: Topological indices; Sombor index; QSPR; Drugs; Regression analysis